The Roles of Extracellular Matrix in Breast Carcinoma: A Narrative Literature Review - Pratama, Eka Putra; Citra Dewi (RSUP Dr Moh Hoesin Palembang, 2022)
The extracellular matrix is a complex and highly dynamic molecular network and serves to provide biochemical signals in the process of development, invasion, and metastasis of breast cancer. There are several proteins that contribute to the structure and function of the extracellular matrix, including collagen, laminin, glycosaminoglycans, and proteoglycans. Alterations of the extracellular matrix in breast cancer are not only limited to the composition of the extracellular matrix but also remodeling enzymes such as matrix metalloproteinase (MMP), cathepsin, urokinase plasminogen activator (uPA), lysyl oxidase (LOX) and heparanase. The extracellular matrix can increase breast cancer progressivity and resistance to treatment, so it is important to know its role because it can be a targeted therapy in the future.